(untitled) (Global Journal of Science Frontier Research, 2017)
Anisotropic property of media is one function which metamaterials make possible for electromagnetic propagation. Hypothetical magnetic currents in the finite difference time domain (FDTD) method create such anisotropy in permeability in numerical models, in similar way to the modeling of Drude-type permitivity for plasma. Numerical results show clear effects of cloaking in which anisotropic permeability is conceivable by experiments.